Calculus (3rd Edition)

Published by W. H. Freeman
ISBN 10: 1464125260
ISBN 13: 978-1-46412-526-3

Chapter 15 - Differentiation in Several Variables - 15.6 The Chain Rule - Preliminary Questions - Page 808: 3



Work Step by Step

Since we have $f(u,v)=rse^{r+s}$, then at $r=1$ and $s=1$, we have: $$f(u,v)=(1)(1)e^{1+1}=e^2.$$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.